2016
DOI: 10.1016/j.jeconom.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the errors: A simple approach for improved volatility forecasting

Abstract: We propose a new family of easy-to-implement realized volatility based forecasting models.The models exploit the asymptotic theory for high-frequency realized volatility estimation to improve the accuracy of the forecasts. By allowing the parameters of the models to vary explicitly with the (estimated) degree of measurement error, the models exhibit stronger persistence, and in turn generate more responsive forecasts, when the measurement error is relatively low. Implementing the new class of models for the S&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
273
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 347 publications
(298 citation statements)
references
References 54 publications
22
273
0
3
Order By: Relevance
“…Bollerslev, Patton, and Quaedvlieg (2016) proposed a simple modification to accommodate this in the context of univariate volatility models, by allowing θ 1 in (6) to depend on an estimate for the measurement error variance:…”
Section: Harq Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bollerslev, Patton, and Quaedvlieg (2016) proposed a simple modification to accommodate this in the context of univariate volatility models, by allowing θ 1 in (6) to depend on an estimate for the measurement error variance:…”
Section: Harq Modelsmentioning
confidence: 99%
“…However, the magnitude of the errors generally decrease with the horizon, and the difficulties in accurately estimating the integrated quarticity may easily outweigh the benefits of adjusting the weekly and monthly coefficients; Bollerslev, Patton, and Quaedvlieg (2016) provides an analysis of the corresponding tradeoffs in the univariate context. 8 separately.…”
Section: Harq-drd Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [14] examines and predicts aggregate volatility, and the researcher developed a model of individual returns to the study of volatility. Reference [15] examined a new class of volatility forecasting models and they noticed significant improvements in the accuracy of the resulting forecasts compared to the forecasts from some of the most popular existing models. They found that the HARQ model is slightly more subtle while the HAR places greater weight on the weekly and monthly lags.…”
Section: Introductionmentioning
confidence: 99%